Doing participant observation in a psychiatric hospital— Research ethics resumed - Oeye, Christine; Bjelland, Anne Karen; Skorpen, Aina (Social science & medicine (1982), 2007)
Social scientists who employ participant observation methods in medical settings are often held accountable for their research methods, specifically in regard to medical research ethics. However, the medical research ethics tradition rubs uneasily against participant observation and the anthropological understanding of the research process. The underlying premise for considering research ethics in the current case is the notion of the vulnerability of psychiatric patients as a participant group. Based on this notion of vulnerability among psychiatric patients, this article discusses the epistemological grounds for vulnerability in anthropological and medical research ethics. The authors draw on their experience with the Regional Committee for Medical Research Ethics in Norway, and the consequences of the guidelines used for participant observation as a research method in a psychiatric hospital. Social science researchers are required to follow medical ethical guidelines, such as informed consent, the principle of voluntariness, and estimation of risks and benefits. Ethnographers have found these guidelines to be obstructive when doing social science research in a psychiatric hospital. The article suggests the need for reformulation of research guidelines for participant observation in medical settings.